Science Is Disruptive, Science of Religion Particularly So - Talmont-Kaminski, Konrad (Journal for the cognitive science of religion, 2019)
White’s book will serve to set the agenda for the cognitive science of religion. One crucial aspect of that agenda is the relationship between this kind of scientific research and theistic commitment. White has been eager to show the two are wholly compatible. However, any serious scientific study of religion is necessarily going to be highly disruptive, making the management of the relationship between science and religion a particularly difficult issue in that question. We show why this is the case and discuss two examples where White’s stated views are not well-justified. The first of these is the naturalist commitment of scientific research, which should be understood as the rejection of supernatural claims based upon a long history of their failure to explain observed phenomena, rather than as the limitation of scientific methods that White sees it as. The second is the issue of secularization, where we have extensive evidence for its rapid progress in developed societies and where the human tendency to supernatural beliefs and practices must be considered in the context of particular environments, despite White’s view that secularization theory has been found wanting.